ANALISIS PERMINTAAN DAN PENAWARAN KOPI DI KALANGAN MAHASISWA - Hizia; Sembiring , Jenari; Aidilia Azzahra, Siti; Syuriani Harahap , Evi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Coffee is one of the commodities that has experienced a significant increase in consumption among society, particularly among young people such as university students. This phenomenon is influenced not only by consumption needs but also by changes in lifestyle and academic activities among students. This study aims to analyze the demand and supply of coffee among students and the factors influencing them. The research method used in this study is a qualitative approach with a library research method by analyzing various literature sources such as scientific journals, books, and academic publications relevant to the research topic. The results show that the demand for coffee among students is influenced by several main factors, including coffee prices, the need to increase concentration in academic activities, social environmental influences, and changes in student lifestyles. Meanwhile, the increasing demand for coffee has encouraged an increase in the supply of coffee products in various forms, such as instant coffee, packaged coffee, and coffee served in modern coffee shops around campus areas. The interaction between demand and supply indicates that coffee has become part of the consumption culture among students. Therefore, the analysis of coffee demand and supply among students demonstrates market dynamics influenced by economic, social, and lifestyle factors of the younger generation.